The Determinants of Efficiency of Higher Education Institutions with Public Service Agency Status in Indonesia - Faizal Angga Nugraha; Imam Subekti; Lilik Purwanti (e-2477-1929)
The purpose of this study is to measure technical efficiency score of Higher Education Institutions (HEI’s) especially Public Service Agencies (PSA) in Indonesia during 2013-2015 and analyse its determinants i.e. non service revenue, Service cost and financial independence. The data were utilized in this research were indigenous secondary data of financial statement 32 PSA's universities, forlap dikti, BAN PT and PPK BLU's directorate report. This research utilized 2 stages, in the first phase was to measure technical efficiency zooms colleges which methods were non parametrik with Data Envelopment Analysis (DEA) approaching VRS'S assumption and input oriented and the second phase used regression tobit's model. The results pointed out that the score of technical efficiency showed an increase in the period of 2013-2015. It means that there is an increase in the number of universities capable of optimizing the whole its resources (input) in producing output gradually towards efficient. Another result showed that the non service revenue, service cost and financial independence had positive affect to the technical efficiency.